2021
DOI: 10.18632/aging.203718
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 9 enhances osteogenic and angiogenic responses of human amniotic mesenchymal stem cells cocultured with umbilical vein endothelial cells through the PI3K/AKT/m-TOR signaling pathway

Abstract: Background: Neovascularization plays an essential part in bone fracture and defect healing, constructing tissue engineered bone that targets bone regeneration. Bone morphogenetic protein 9 (BMP9) is a regular indicator that potentiates osteogenic and angiogenic differentiation of MSCs. Objectives: To investigate the effects of BMP9 on osteogenesis and angiogenesis of human amniotic mesenchymal stem cells (hAMSCs) cocultured with human umbilical vein endothelial cells (HUVECs) and determine the possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Neovascularization is crucial for the repair of bone defects and fractures. 38 It was clear from the results that the TN was significantly decreased in all treated groups, which enclosed newly formed bone marrow compared with the control group. Our results are in accordance with those of Toru et al, 23 who found that osteogenesis and angiogenesis were stimulated by Ang1, which is expressed by osteoblasts.…”
Section: Discussionmentioning
confidence: 75%
“…Neovascularization is crucial for the repair of bone defects and fractures. 38 It was clear from the results that the TN was significantly decreased in all treated groups, which enclosed newly formed bone marrow compared with the control group. Our results are in accordance with those of Toru et al, 23 who found that osteogenesis and angiogenesis were stimulated by Ang1, which is expressed by osteoblasts.…”
Section: Discussionmentioning
confidence: 75%
“…PI3K/Akt/mTOR pathway plays an important role in regulating the osteoblastic differentiation spurred by BMP9. 30 However, the precise regulatory roles of mTORC1 and mTORC2 in this process remain unclear. PCR results revealed that Raptor and Rictor were both up-regulated by BMP9 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 52 , 53 Activation of this pathway promoted the pre-osteoblasts and BMSCs differentiate into osteoblasts, whereas targeted inhibition suppressed the bone formation in vivo and in vitro . 54 BMP9 osteogenic potency can be promoted by activating PI3K/AKT signal, 30 , 55 although the detailed molecular mechanism required further analysis. As downstream targets of PI3K/AKT, both mTOR and GSK-3β contribute to cell growth regulation and protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway plays a key role in regulating cells under physical stimulation [51]. The signaling [52][53][54][55] found that modulating the cytoskeleton using perturbing drugs changes signal transduction and the differentiation tendency of mesenchymal stem cells. Gu et al [56] found that the surface-modified titanium matrix can promote the secretion of bone calcium matrix by mesenchymal stem cells through the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%